Knowledge, attitudes, practices and barriers related to cervical cancer, screening and human papilloma virus (HPV) vaccination among female non-health professionals in the Offinso South Municipality, Ashanti Region, Ghana. - Buadu, Fred Kwesi Dr. (2017)
A thesis submitted to the Department of Health Policy, Management and Economics, College of Health Sciences, School of Public Health, in partial fulfilment of the requirements for the degree of Master of Public Health in Health Services Planning and Management,